Escape from Macau - Morrison, Keith (Macau Business, 2022)
Macau, Macau Business, MAG, MB, MB Featured, Opinion | Macau used to be very appealing to expatriates from across the world. Its low tax rate (and zero tax for low-paid expatriates), blends of cultures, business opportunities, life style, history, unique features and a host of other attractions fuelled an ongoing supply of foreign nationals to this small, unusual city. It is an interestingly idiosyncratic place in which to live. For many expatriates, Macau has been home, in many cases reaching back more than one generation. This is perhaps unsurprising, as people here are typically exquisitely polite, a delight to be with, and very accepting. Its acceptance of differences in values is an example to countries across the world. Macau is a safe place to live.
Section: Macau